Abnormal anxiety- and depression-like behaviors in mice lacking both central serotonergic neurons and pancreatic islet cells - Jia, Yun-Fang; Song, Ning-Ning; Mao, Rong-Rong; Li, Jin-Nan; Zhang, Qiong; Huang, Ying; Zhang, Lei; Han, Hui-Li; Ding, Yu-Qiang; Xu, Lin (Frontiers in Behavioral Neuroscience, 2014)
Dysfunction of central serotonin (5-HT) system has been proposed to be one of the underlying mechanisms for anxiety and depression, and the association of diabetes mellitus and psychiatric disorders has been noticed by the high prevalence of anxiety/depression in patients with diabetes mellitus. This promoted us to examine these behaviors in central 5-HT-deficient mice and those also suffering with diabetes mellitus. Mice lacking either 5-HT or central serotonergic neurons were generated by conditional deletion of Tph2 or Lmx1b respectively. Simultaneous depletion of both central serotonergic neurons and pancreatic islet cells was achieved by administration of diphtheria toxin (DT) in Pet1-Cre;Rosa26-DT receptor (DTR) mice. The central 5-HT-deficient mice showed reduced anxiety-like behaviors as they spent more time in and entered more often into the light box in the light/dark box test compared with controls; similar results were observed in the elevated plus maze test. However, they displayed no differences in the immobility time of the forced swimming and tail suspension tests suggesting normal depression-like behaviors in central 5-HT-deficient mice. As expected, DT-treated Pet1-Cre;Rosa26-DTR mice lacking both central serotonergic neurons and pancreatic islet endocrine cells exhibited several classic diabetic symptoms. Interestingly, they displayed increased anxiety-like behaviors but reduced immobility time in the forced swimming and tail suspension tests. Furthermore, the hippocampal neurogenesis was dramatically enhanced in these mice. These results suggest that the deficiency of central 5-HT may not be sufficient to induce anxiety/depression-like behaviors in mice, and the enhanced hippocampal neurogenesis may contribute to the altered depression-like behaviors in the 5-HT-deficient mice with diabetes. Our current investigation provides a novel insight into understanding the relationship between diabetes mellitus and psychiatric disorders.